Association and gene–gene interaction analyses for polymorphic variants in CTLA-4 and FOXP3 genes: role in susceptibility to autoimmune thyroid disease - Fathima, Nusrath; Narne, Parimala; Ishaq, Mohammed (Endocrine, 2019)
Purpose Polymorphic variants of cytotoxic T-lymphocyte antigen-4 ( CTLA-4 ) and forkhead box protein P3 ( FOXP3 ) genes are implicated in dysregulated immune homeostasis and autoimmune disorders. We analyzed the association between CTLA-4 rs231775 and FOXP3 rs3761548, rs3761549 polymorphisms and predisposition to autoimmune thyroid disease (AITD), inclusive of Hashimoto’s thyroiditis (HT) and Graves’ disease (GD) in South-Indian population. Methods A total of 355 AITD subjects (comprising 275 HT and 80 GD) and 285 randomly selected age- and sex-matched control subjects were genotyped for the aforementioned polymorphisms by PCR-RFLP method. Results The rs231775 “G” allele was preponderant in HT and GD subjects when compared with controls and exerted a dominant influence on the susceptibility to HT ( p = 0.009) and GD ( p = 0.02), respectively. There was no allelic association of rs3761548 and rs3761549 polymorphisms with AITD susceptibility, albeit a significant difference in genotype distribution with respect to rs3761549. Haplotype analysis revealed an increased frequency of rs3761548 “C”–rs3761549 “T” in HT and GD subjects, thereby associating it with disease predisposition ( p = 0.03). Epistatic interaction analysis by multifactor dimensionality reduction approach revealed redundancy between CTLA-4 and FOXP3 genes in influencing the susceptibility to AITD. Conclusions The genetic variation in CTLA-4 gene with reference to rs231775 polymorphism contributes to an increased predisposition to HT and GD. Also, in conjunction with FOXP3 gene variants it seems to influence the susceptibility to HT and GD respectively. The significance of these findings in combination with antithyroid antibody screening could plausibly contribute towards meticulous case-finding for effective treatment of HT and GD.